ANALISA PENGARUH DILATASI DENGAN BALOK KANTILEVER TERHADAP STRUKTUR GEDUNG KANTOR 2 LANTAI - Amami, Luthfia; Masril, Masril; Habirun, Asiya Nurhasanah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Indonesia is an area that is on the path of the most active earthquakes in the world because it is on the Pacific Ring of Fire. From a tectonically active perspective, Indonesia has a great chance of having a large potential earthquake at this time or someday. The movement of tectonic plates causes the earth's surface to sway so that buildings standing above the earth's surface experience physical damage and can even threaten human life. So to prevent horizontal displacement of the building structure, it must be dilated in order to reduce the irregularity of the building. Analysis of linear buildings where buildings are located in areas with high earthquake risk, namely Payakumbuh City, West Sumatra. The analysis aims to determine the behavior of the dilated structure so that the horizontal displacement of the building which results in collisions between buildings can be known, the effective dilation distance is used. Analysis was carried out on 4 structural models where the first model is a structure that uses dilation, models two and three are separations of intact buildings each of which is given cantilever beam dilation, and the fourth model is a structure without using dilation. To make it easier to calculate the expected parameters, the analysis is assisted by a structural analysis program, namely SAP 2000 version 14. The earthquake data used refers to the Payakumbuh City Response Spectrum data.